Improving Access in Gastroenterology: The Single Point of Entry Model for Referrals - Kerri L Novak; Sander Veldhuyzen Van Zanten; Sachin R Pendharkar (Canadian Journal of Gastroenterology)
In 2005, a group of academic gastroenterologists in Calgary (Alberta) adopted a centralized referral intake system known as central triage. This system provided a single point of entry model (SEM) for referrals rather than the traditional system of individual practitioners managing their own referrals and queues. The goal of central triage was to improve wait times and referral management. In 2008, a similar system was developed in Edmonton at the University of Alberta Hospital (Edmonton, Alberta). SEMs have subsequently been adopted by numerous subspecialties throughout Alberta. There are many benefits of SEMs including improved access and reduced wait times. Understanding and measuring complex patient flow systems is key to improving access, and centralized intake systems provide an opportunity to better understand total demand and system bottlenecks. This knowledge is particularly important for specialties such as gastroenterology (GI), in which demand exceeds supply. While it is anticipated that SEMs will reduce wait times for GI care in Canada, the lack of sufficient resources to meet the demand for GI care necessitates additional strategies.